Efeito de diferentes fotopolimerizadores e meio de imersão na rugosidade e na cor de um compósito nanoparticulado - Plaster, Suéllen Campos; Peixoto, Letícia Monteiro; Guedes, Ana Paula Albuquerque; Silva, Daniela Nascimento; Castro, Martha Chiabai Cupertino (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction The excessive consumption of soft drinks seems to change the properties of composites and may be associated with the light curing unit.Objective To evaluate changes in surface roughness (ΔR) and color (ΔE) of one composite polymerized with different light sources, immersed in distilled water or in Coca-Cola®.Methodology Sixty samples of nanofilled resin (FiltekMR Z350 XT, 3M) were distributed into following light curing units: a) quartz-tungsten-halogen (QTH) light; b) light emitting diode (LED) with polymer tip (LED 1) and c) LED with optic fiber tip (LED 2). Half of each group (n=10) was kept in water or immersed in Coca-Cola® for 20 minutes 2x/day during 14 days. Data were submitted to the Mann-Whitney and Kruskal-Wallis tests (p≤0.05).Result The ΔR was not significant among groups: in water: QTH = 0.006; LED 1 = 0.019; LED 2 = 0.010 (p=0.33); in soft drink: QTH = 0.021; LED 1= 0.011; LED 2 = 0.030 (p=0.86). The ΔE was not significant among light curing units: in water: QTH = 1.40; LED 1 = 1.80; LED 2 = 1.60 (p=0.31); in soft drink: QTH = 2.51; LED 1= 1.91; LED 2 = 2.61 (p=0.41), but was significant compared the immersion media (p=0.01), except for LED 1 (p=0.54).Conclusion The light curing lights did not interfere with the surface roughness and with color of nanofilled composite. Daily dives in soft drinks did not change smoothness, but the color changed to visually perceptible way, though clinically acceptable, according to the scientific literature parameters.

ResumoIntrodução O consumo excessivo de refrigerantes parece alterar as propriedades dos compósitos e essa alteração pode estar relacionada à unidade fotopolimerizadora.Objetivo Avaliar a alteração da rugosidade superficial (ΔR) e da cor (ΔE) de um compósito polimerizado por diferentes fotopolimerizadores, imerso em água destilada ou Coca-Cola®.Metodologia Sessenta amostras da resina nanoparticulada (FiltekMR Z350 XT, 3M) foram distribuídas de acordo com as diferentes unidades de fotopolimerização: a) luz halógena de quartzo-tungstênio-halogênio (QTH); b) Luz de Emissão Diodo - LED 1 com ponteira de polímero; c) LED 2 com ponteira de fibra ótica. Metade de cada grupo (n=10) foi mantida em água destilada ou imersa em Coca-Cola® 2×/dia por 20 minutos, durante 14 dias. Os dados foram submetidos aos testes Mann-Whitney e Kruskal-Wallis (p≤0,05).Resultado A ΔR não foi significante entre os grupos: em água: QTH = 0,006; LED 1 = 0,019; LED 2 = 0,010 (p=0,33); em refrigerante: QTH = 0,021; LED 1= 0,011; LED 2 = 0,030 (p=0,86). A ΔE não foi significativa entre os fotopolimerizadores: em água: QTH = 1,40; LED 1 = 1,80; LED 2 = 1,60 (p=0,31); em refrigerante: QTH = 2,51; LED 1= 1,91; LED 2 = 2,61 (p=0,41), mas foi significante comparando os meios de imersão (p=0,01), exceto para LED 1 (p=0,54).Conclusão As unidades fotopolimerizadoras não interferiram na rugosidade superficial e na cor da resina composta nanoparticulada. Os mergulhos diários em refrigerante não alteraram a lisura, mas alteraram a cor de modo visualmente perceptível, mas clinicamente aceitável, conforme os parâmetros da literatura científica.
Effect of different light curing units and immersion media on roughness and color of a nanofill composite
Keywords: Composite resins; photopolymerization; color; surface properties; Resinas compostas; fotopolimerização; cor; propriedades de superfície